FORTALECIMIENTO TURÍSTICO DEL PLAN DE DESARROLLO Y ORDENAMIENTO TERRITORIAL DE LA PARROQUIA URBANA DE GONZANAMÁ, CANTÓN GONZANAMÁ, PROVINCIA DE LOJA - Jaramillo Tenenpaguay, Jhonatan Jayron (2019)
The objective of this work is to "Strengthen the Plan of Development and Territorial Planning for the Urban Parish Gonzanamá, Cantón Gonzanamá, Loja Province ". The methodology used is the Ricaurte, it allows to know the local reality and the needs that a specific sector requires; also developed files of the tourist attractions in the town using the MINTUR methodology, In the same way, a direct observation of the reality was made, with the purpose of carrying out a study and in the future to boost them touristically. Then a participatory workshop in conjunction with the local community and the parish authorities was made, in order to validate the information obtained based on the current situation of infrastructure, attractions and tourist services; once the tourism needs were determined, a second participatory workshop was developed with the objective of making tourism development proposals selected by the locality, which will allow the sector and the population to publicize their potential tourism. The development of this work allowed to determine, that the parish has several services for the visitor such as: accommodation, food, recreation and others. It also has infrastructure that allow the good living of the population as well as the people who visit the sector. In terms of activities and tourism skills in the community you can also find a minimum of people who devote their time to develop activities linked to tourism, because according to the perception of people tourism is an alternative and seasonal economic activity that It only develops in high season. It was also determined that the majority of tourist attractions are Hierarchy II, these make possible the touristic, economic, social and cultural development. Therefore, several strategic objectives were established such as: tourism product, tourist training to the community, management of tourism planning in 5 the GAD, promotion and publicity that allow analyzing the potential and executing the parish touristic promotion, affirming the tourist wealth that has Gonzanamá, it is established that it has enough natural and cultural wealth to generate tourism, therefore the main strategies to be developed in this research are related to the needs that are generated internally and externally in the parish, these being tools that provide the general guidelines for tourism management and local tourism development. Finally, concluded that the parish has the potential to be a competitive tourist destination; for the services, accessibility and tourist attractions it offers, and only a tourist advance will be achieved if it is properly managed and worked in conjunction with the community, they are the direct link between the visitor and the local tourist wealth.